The effect of attitudes, subjective norms and perceived security and privacy on the use of SMS banking among bank customers in Johor / Nur Nabila Husna Zanal Abdin - Zanal Abdin, Nur Nabila Husna (Faculty of Business and Management, 2019)
SMS banking has been introduced and implemented in Malaysia since 2006. However, the justification on customer's intention towards the usage of SMS banking is still unknown. This study is conduct with several variables which are attitudes, subjective norms and perceived security and privacy that affect the intention to use SMS banking. Quantitative method has been used in this research to study the customer's intention towards the use of SMS banking. 1 15 questionnaires have been distributed to the respondents based on the identification of customers who use SMS banking. In order to achieve the research objective which is to determine the factors that influence the intention to use SMS banking among bank customers in Johor, researcher used F-Test (whole analysis), T-Test (partial analysis) and Pearson Correlation. Through F-Test, the factor of attitudes, subjective norms and perceived security and privacy were identified to have a positive significant that affect the intention to use the SMS banking among bank customers in Johor. Through T-Test, factors of independent variables that affect the intention to use SMS banking can be identified and measured. Pearson Correlation is used to identify positive significant relationship between independent variables and dependent variables. Based on data analysis received from the respondents who used SMS banking, it can identified that overall factors of attitudes, subjective norms and perceived security and privacy gives positive significant effect the intention to use the SMS banking.